Security Risk and Breach Detection Approach Based Blockchain for Medical Applications - Mohammed Amin Almaiah; Aitizaz Ali; Tayseer Alkhdour; Abdalwali Lutfi (IEEE Access)
Several cloud-based applications are used for digital healthcare data allocation, but such an approach relies on third-party software such as the cloud. Existing models mainly utilize blockchain as a data storage tool rather than a security platform. Biomedical and monitoring devices generate massive amounts of data, and the existing approach overloads the blockchain with IoT data. This research proposes blockchain as a unique method for securing patient-related data access and integrating homomorphic encryption with an end-to-end privacy-protecting system. In this research, we propose a blockchain-based architecture for identifying security threats in personal medical devices to address the existing issues related to healthcare devices. The proposed framework uses certificate authority to assign an access control token in order to access a particular session. A certificate authority is the nodes based on the reputation within the blockchain network elected through consensus protocol. Proposed framework uses dual certificate authorities, which leads to more reliability and security if one certificate authority is down. Moreover, the existing algorithm overburden the medical devices which are resource constraint such as power oriented and such approaches leads to storage and communication cost overhead. By minimizing latency, security, and data ownership, the proposed framework outperforms the existing centralized system, by comparing the framework and evaluating its performance with the benchmark models.